2016
DOI: 10.1016/j.celrep.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C Orchestrates Glioblastoma Angiogenesis by Modulation of Pro- and Anti-angiogenic Signaling

Abstract: High expression of the extracellular matrix component tenascin-C in the tumor microenvironment correlates with decreased patient survival. Tenascin-C promotes cancer progression and a disrupted tumor vasculature through an unclear mechanism. Here, we examine the angiomodulatory role of tenascin-C. We find that direct contact of endothelial cells with tenascin-C disrupts actin polymerization, resulting in cytoplasmic retention of the transcriptional coactivator YAP. Tenascin-C also downregulates YAP pro-angioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 38 publications
1
72
1
Order By: Relevance
“…Tenascin-C exerts a dual role in angiogenesis. Whereas tenascin-C blocks prosurvival signaling in endothelial cells through direct contact, it also induces a pro-angiogenic secretome in glioblastoma cells (Rupp et al, 2016). Tenascin-C can also promote survival of circulating breast cancer cells and their colonization within lung parenchyma; this involves Notch and Wnt signaling, including stemnesspromoting leucine-rich-repeat-containing G-protein-coupled receptor 5 (LGR5) (Oskarsson et al, 2011).…”
Section: Regulation Of Tnc Gene Expressionmentioning
confidence: 99%
“…Tenascin-C exerts a dual role in angiogenesis. Whereas tenascin-C blocks prosurvival signaling in endothelial cells through direct contact, it also induces a pro-angiogenic secretome in glioblastoma cells (Rupp et al, 2016). Tenascin-C can also promote survival of circulating breast cancer cells and their colonization within lung parenchyma; this involves Notch and Wnt signaling, including stemnesspromoting leucine-rich-repeat-containing G-protein-coupled receptor 5 (LGR5) (Oskarsson et al, 2011).…”
Section: Regulation Of Tnc Gene Expressionmentioning
confidence: 99%
“…Tumor-derived TNC promotes or enhances the process of angiogenesis in different tumor models (Hirata et al , 2009; Kawamura et al , 2018; Pezzolo et al , 2011; Rupp et al , 2016), but the mechanistic insight has not been fully elucidated. In our previous study, TNC level is much higher in high metastatic potential CRC cell line SW620 compared to the other four CRC cell lines, particularly in the conditioned medium (Li et al , 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In our findings, TNC was implicated in focal adhesion, PI3K/Akt signaling pathway and EMT. Several researchers have demonstrated that TNC promotes neoplastic angiogenesis in various cancers including breast cancer, glioblastoma, and oral and pharyngeal squamous cell carcinoma (Atula et al , 2003; Mai et al , 2002; Rupp et al , 2016). However, few reports have investigated the expression of TNC in VECs of CRC and the mechanism for promoting CRC angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Fbln7, which was identified as an ECM molecule in developing teeth, is expressed in both antiangiogenic tissue cartilage and angiogenesis‐related and immunoprivileged tissues such as the eye and placenta, and the C‐terminal fragment of Fbln7 exerts antiangiogenic activity . Matricellular proteins such as Fbln3 and tenascin‐C are reported to promote angiogenesis in GBM by modulating the proangiogenic and antiangiogenetic signaling . To date, however, little information is available for which grade or cell type in glioma tissues is responsible for Fbln7 production or its functional role in GBM angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Matricellular proteins such as Fbln3 and tenascin-C are reported to promote angiogenesis in GBM by modulating the proangiogenic and antiangiogenetic signaling. 22,23 To date, however, little information is available for which grade or cell type in glioma tissues is responsible for Fbln7 production or its functional role in GBM angiogenesis.…”
Section: Introductionmentioning
confidence: 99%